The symptoms of surface dyslexia in Arabic: the impact of orthographic ambiguity on reading abilities of a patient with Alzheimer's disease. - Boumaraf, Assia; Brahimi, Souad; Ladjali, Samia; Macoir, Joël (Clinical Linguistics & Phonetics, 2024)
Like other Semitic languages, Arabic is known for its rich morphology and consonantal writing system. In this article, we report the first case of acquired surface dyslexia in an Arabic-speaking patient (HBS). Surface dyslexia is characterised by difficulty reading irregularly spelled words, while performance is better with regular words and nonwords. The purpose of this study was to describe the symptoms of surface dyslexia in Arabic and to investigate how orthographic depth may affect reading in the context of semantic impairment. In HBS, who had Alzheimer's disease, reading was impaired for both words and nonwords. Her reading performance was affected by orthographic ambiguity and by the presence of diacritics depicting short vowels. In particular, she produced mainly vowel errors, suggesting an overreliance on the sublexical route of reading. On the other hand, HBS was able to distinguish long vowels from consonants represented by the same letters, provided there was a real root. This finding can be taken as evidence that HBS could access the word's root to decide whether the vowel letter represents a long vowel or a consonant. The results of this study suggest that the characteristics of surface dyslexia appear to be universal: reading regular words is spared compared to irregular words and non-words. However, the error patterns that HBS showed in reading support a language-specific conceptualisation of the processing components of the lexical and sublexical routes of reading.